2013
DOI: 10.1002/dmrr.2462
|View full text |Cite
|
Sign up to set email alerts
|

Screening for people with glucose metabolism disorders within the framework of the DEMOJUAN project (DEMOnstration area for primary prevention of type 2 diabetes, JUAN Mina and Barranquilla, Colombia)

Abstract: In total, 2% of all 14 193 screened participants had undetected T2D and 7% GMD. This figure would potentially be 4.6% (T2D), respectively 15% (GMD) if all with a FINDRISC>12 attend the OGTT. Thus, we found the FINDRISC to be a useful tool to identify people with GMD. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
21

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 0 publications
0
14
0
21
Order By: Relevance
“…Whereas the FINDRISC is already part of the Finnish National Diabetes strategy [11], other countries use Type 2 diabetes screening tools in only some parts of the primary health care system [17,[20][21][22]. Population testing of blood glucose is not recommended as it is not sure whether the prognosis of Type 2 diabetes can be improved by early detection and treatment [23,24].…”
Section: Discussionmentioning
confidence: 98%
“…Whereas the FINDRISC is already part of the Finnish National Diabetes strategy [11], other countries use Type 2 diabetes screening tools in only some parts of the primary health care system [17,[20][21][22]. Population testing of blood glucose is not recommended as it is not sure whether the prognosis of Type 2 diabetes can be improved by early detection and treatment [23,24].…”
Section: Discussionmentioning
confidence: 98%
“…Existing screening tools like HbA1c testing or oral glucose tolerance tests can be cost-prohibitive or unavailable due to lack of necessary reagents or testing equipment in lowresource settings. One study in Colombia showed that the use of a non-invasive, easy to administer risk-assessment tool (FINDRISC) could be used to identify individuals who have a high risk of diabetes and could benefit from diabetes prevention [61]. Other risk scores (e.g., the Indian Diabetes Risk Score [MDRF-IDRS] [62]) have been shown in other settings to be similarly effective and cost-effective tools for screening.…”
Section: Diabetes Prevention Modelsmentioning
confidence: 97%
“…En Barranquilla la prevalencia de DM2 en población de 18 a 69 años en el año 2015 fue de 2.58 %, (Alcaldía de Barranquilla, 2016). El estudio de validación del Test de Findrisc realizado en varios centros de atención de salud en la Ciudad, mostró una prevalencia de DM2 del 13%, 18% en hombres y 12% en mujeres (Barengo, 2013). La DM2, es una enfermedad crónica de alta morbilidad y mortalidad en el mundo, de tipo endocrino -metabólica; su etiología compleja, se caracteriza por hiperglucemia debida a una deficiente secreción o acción de la insulina.…”
Section: Introductionunclassified